Intra-varietal Agronomical Variability in Vitis vinifera L. cv. Cannonau Investigated by Fluorescence, Texture and Colorimetric Analysis - Mercenaro, L.; Usai, G.; Fadda, C.; Nieddu, G.; del Caro, A. (South African Journal of Enology and Viticulture, 2016)
To date, innovative, rapid and non-invasive techniques have been used to assess variations in morphological and technological characteristics between grape cultivars. In order to improve knowledge of the qualitative expression of the genetic traits of cv. Cannonau (syn. Grenache), fluorescence, texture and colorimetric analyses were performed on 85 biotypes attributable to this variety. Eighty-five Cannonau biotypes cultivated in the same vineyard were analysed in order to evaluate their morphological and agronomical characteristics. As regards the morphological traits, of the six descriptors observed, five were able to discriminate the Cannonau population according to different expression levels. Must composition, berry colour (using the Minolta tristimulus colorimeter), texture (assessed using the TaxT2i plus texturimeter) and fluorescence (using the Multiplex III detector) were determined on clusters harvested at the same time. Cluster analysis was able to separate the Cannonau population into five groups, characterised by differences in the following criteria: L*, a* and b*, berry skin thickness, FERARI, TSS, pH and titratable acidity, total polyphenols and total anthocyanins. The FERARI index was highly and positively correlated with total anthocyanins and negatively correlated with grape colour, while berry weight and berry skin thickness were not correlated with any variable assessed. The remarkable intra-variability encountered for the qualitative and quantitative characters in the Cannonau variety suggests that new biotypes could be selected for different oenological purposes, using techniques such as the measure of fluorescence and colorimetry. This is the first study carried out within the cv. Cannonau using innovative and classical techniques suitable to investigate intra-varietal variability.